2022 International Joint Conference on Neural Networks (IJCNN) 2022
DOI: 10.1109/ijcnn55064.2022.9891992
|View full text |Cite
|
Sign up to set email alerts
|

Development of Deep Learning approaches to predict relationships between chemical structures and sweetness

Abstract: The non-caloric sweeteners market is catching up with the market of conventionally used sugars due to the benefits of preventing obesity, tooth decay and other health problems. Developing strategies for designing easier-to-produce novel molecules with a sweet taste and less toxicity are up-todate motivations for the food industry. In this sense, Machine Learning (ML) approaches have been reported as cutting-edge technologies to guide the design of new molecules towards specific objectives, including sweet tast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Moreover, the flexibility offered by Tensorflow enables integration of any DL architecture into DeepMol ’s pipeline. By consolidating these capabilities, DeepMol serves as a comprehensive and versatile framework, facilitating implementation and comparison of various ML and DL models in one unified platform [41, 42].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the flexibility offered by Tensorflow enables integration of any DL architecture into DeepMol ’s pipeline. By consolidating these capabilities, DeepMol serves as a comprehensive and versatile framework, facilitating implementation and comparison of various ML and DL models in one unified platform [41, 42].…”
Section: Methodsmentioning
confidence: 99%
“…They demonstrated that consistently highlighted features were known to be associated with drug response. Capela et al [42] conducted a study in which they trained and evaluated 66 different model configurations to predict the relationships between chemical structures and sweetness. Throughout the study pipeline, DeepMol was utilized for several tasks, such as molecular standardization, feature generation, feature selection, model construction, hyperparameter tuning, and model explainability.…”
Section: Practical Applications Of Deepmolmentioning
confidence: 99%